Turleania rubriguttatus, a new species of pagurid hermit crab (Decapoda: Anomura: Paguroidea) from shallow water in Japan, with notes on T. senticosa (McLaughlin & Haig, 1996) - Komai, Tomoyuki (Zootaxa, 2020)
A new species of the pagurid hermit crab genus Turleania McLaughlin, 1997, T. rubriguttatus, is described on the basis of two specimens, including one male and one female, from shallow subtidal waters in Kochi Prefecture, Japan. The new species appears close to T. albatrossae (McLaughlin & Haig, 1996), known from the Philippines, but the proximally unarmed dorsal surface of the right chela palm and the lack of a dorsomesial row of spines on the left cheliped carpus easily distinguish T. rubriguttatus n. sp. from T. albatrossae. Examination of the type material of T. similis Komai, 1999 and T. spinimanus Komai, 1999, and supplemental material from Japan, confirms that the two taxa are synonymous with T. senticosa (McLaughlin & Haig, 1996), as was suggested by previous authors. Re-examination clarified that in T. senticosa the maxilliped 3 has no developed arthrobranchs, and this led the author to assess the status of T. sinensis Han, Sha & An, 2016, which is also synonymised with T. senticosa.